2016
DOI: 10.3928/01477447-20160714-01
|View full text |Cite
|
Sign up to set email alerts
|

The 50 Most Cited Articles in Rotator Cuff Repair Research

Abstract: Analysis of the number of citations within a given specialty provides information on the classic publications of that specialty. The goals of this study were to identify the 50 most cited articles on rotator cuff repair and to analyze various characteristics of these articles. The ISI Web of Science (Thomson Reuters, Philadelphia, Pennsylvania) was used to conduct a search for the term rotator cuff repair. The 50 most cited articles were retrieved, and the following objective characteristics of each article we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 18 publications
(27 reference statements)
8
46
1
Order By: Relevance
“…Namdari et al 22 demonstrated that the majority of the top 50 cited articles in shoulder surgery were published in the 1990s (n = 18) and 1980s (n = 17). Additionally, a study by Kraeutler et al, 16 which assessed the top 50 cited articles in rotator cuff surgery, showed 29 articles published in the 2000s and 16 published in the 1990s. 22 Kraeutler et al 16 had similar results as in the present study, with most articles published in the 2000s (n = 30) and 1990s (n = 17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Namdari et al 22 demonstrated that the majority of the top 50 cited articles in shoulder surgery were published in the 1990s (n = 18) and 1980s (n = 17). Additionally, a study by Kraeutler et al, 16 which assessed the top 50 cited articles in rotator cuff surgery, showed 29 articles published in the 2000s and 16 published in the 1990s. 22 Kraeutler et al 16 had similar results as in the present study, with most articles published in the 2000s (n = 30) and 1990s (n = 17).…”
Section: Discussionmentioning
confidence: 99%
“…The Web of Science and Scopus online databases were searched in December 2017 according to previously described methods without date restrictions. 3 , 16 , 17 , 29 The terms “rotator cuff repair,” “rotator cuff surgery,” “arthroscopic rotator cuff repair,” and “arthroscopic rotator cuff surgery” were individually searched in each database. All articles and all journals were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our selection of 50 articles was arbitrarily selected based on prior citation analyses across orthopaedic and other clinical subspecialties. 11,13,[15][16][17][18] In contrast to prior analyses in the literature, our study looks across several diagnoses rather than a single pathology, which inherently led to a larger initial subset of articles requiring analysis for the subsequent inclusion in our list. To establish a manageable compilation of articles to be used for educational purposes, the selection of 50 articles was deemed appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Using similar techniques, studies have been conducted with similar aims across several orthopaedic subspecialties such as shoulder surgery, pediatric orthopaedic surgery, fracture surgery, anterior cruciate ligament (ACL) research, and rotator cuff repair research. 13 14 15 16 17 To our knowledge, no investigation on the most-cited works on lateral epicondylitis, or “tennis elbow,” has been performed; this is a subject in which treatment strategies continue to be debated by experts today. The purpose of this study was to determine the 50 most-cited articles on lateral epicondylitis and to better characterize these works as a way to evaluate the current literature on this common orthopaedic condition.…”
mentioning
confidence: 99%